Role of boron mineral size on thermal, microstructural and mechanical characteristic of IPP - Uğur Soykan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study paves to way to investigate the fundamentalcharacteristics including the crystalline melting temperature, percent crystallinity,crystal structure, unit cell parameters, crystal size, mechanical behaviour,ultimate strength, Modulus and impact strength in the IPP based compositesformed by blending of IPP with the varying content levels (5, 10, 15, 20 and30%) of ulexites having different particle sizes (45 and 75µm). Thecharacterizations of the prepared IPPbased composites containing ulexite were performed by means of conventionalmeasurement methods such as Differential Scanning Calorimeter (DSC), X-raydiffractions and several mechanical tests. The obtained results depicted thatthe content and particle size of boron mineral presenting in IPP basedcomposites had significant effects on the crucial properties of IPP. Namely,the crystalline melting temperature of IPP increased initially (165.46°C to168.54°C) when adding 5% of 45µm ulexite into IPP and then, dramatic decreasewas observed with the content increment. The addition of 75µm ulexite into toIPP matrix led to consistent decreasing of crystalline melting temperatures ofIPP domains. Furthermore, a and b unit cell dimensions of monoclinicstructures initially showed the expansions, but then contracted consistentlywith the increasing of ulexite content. The serious decrement in c unit cellparameter was observed with the increasing of ulexite content for the bothparticle sizes.Moreover, the remarkable reinforcements were achieved in theultimate strengths, Young's Modulus and impact strength of the IPP basedcomposites. The maximum improvements in mechanical properties were obtainedwith the composites containing 5% of 45µm ulexite and mainly 15% of 75µmulexite. These developments presumably were caused from advance in thealignments and orientations of the IPP chains in the matrix due to presence ofulexite particles.